The feasibility of low mechanical index contrast enhanced ultrasound (CEUS) in distinguishing malignant from benign thoracic lesions - Qureshi, Nagmi R.; Hintze, Christian; Risse, Frank; Kopp-Schneider, Annette; Eberhardt, Ralf; Kauczor, Hans-Ulrich; Delorme, Stefan (Ultrasound in medicine & biology, 2011)
We proposed to assess the feasibility of low mechanical index (MI) contrast enhanced ultrasound (CEUS) in the characterisation of thoracic lesions. Fifty patients were prospectively examined by CEUS and images acquired on a low MI (0.17-0.24) setting following injection of SonoVue. From region-of-interest (ROI) generated signal intensity (SI) time curves, the maximum SI, bolus arrival time (BAT), time to peak intensity (TTP), wash-in slope and mean transit time (MTT) were calculated. Using the Wilcoxon rank test; parameters and threshold values for positive differentiation were determined. In addition, for the parameters that allowed positive differentiation between malignant and benign lesions receiver operator curves (ROC) were obtained. The wash-in slope, TTP and MTT (p = 0.0003, <0.0001, 0.02) allowed positive differentiation. The sensitivity and specificity was 93% and 78%, with 6.87 s(-1) threshold value for the wash-in slope, 78% and 89% with 11.84 s threshold for the TTP and 48% and 89% with 78.6 s threshold for the MTT. CEUS is a useful tool for differentiating malignant and benign thoracic lesions.
Gesehen am 23.01.2023